Stability Data Xbee S2b Zigbee Communication on Arduino Based Sumo Robot - I Made Aditya Nugraha; I Gusti Made Ngurah Desnanjaya; I Wayan Dani Pranata; Wawan Harianto (Journal of Robotics and Control (JRC), 2021)
Wireless technology is a solution to reach hard-to-reach places using cable technology. The use of wireless technology can reach these areas without using copper or cables in the data transmission process. Communication technology using wireless is one solution to connect the control system to support the creation and achievement of the goals of the 4.0 revolution so that control and monitoring become easier. With the convenience provided by wireless technology such as connecting various types of system devices between other systems. One type of wireless technology is WPAN, especially on the ZigBee system from Digi International with the IEEE 802.15.4 protocol standard with low power consumption and working at a frequency of 2.4 GHz. Utilization of the communication system from the ZigBee protocol can control according to the range capabilities of the ZigBee system. ZigBee's ability and use of communication can perform communication control robot sumobot (slave robot) and remote control (robot leader) as an introduction to command data to carry out movements on the slave robot in accordance with the orders from the robot leader After trying XBEE to send data at a certain distance without experiencing data loss, the best distance is obtained, namely 1 - 100 meters with the firmware coordinator and router settings. Data delays can be minimized with a transfer rate of 3 kbps in the data transfer rate.